Representasi Budaya Melayu dalam Video Musik ‘Tujuan Hidup Bukan Dunia’ - Fikri Fikri; Fenny Tri Siah; Astrid Yulinda Putri; Chrisnatama Tangguh Prasetyo; Muhammad Rizqy Al-Mubarok (SPHOTA: Jurnal Linguistik dan Sastra, 2026)
This research is a qualitative descriptive study with song lyrics and audio-visual activities in music videos as codes for the object of research. The observation method is conducted to collect the research object, which is further analyzed based on semiotic studies by applying Umberto Eco's theory. This study aims to classify the code and describe the relationship between content and expression in the code in order to understand the intentions of the songwriters represented through the embodiment of Malay culture. The result shows song lyrics, music, traditional customs, nature, traditional houses, and accessories as a code containing content and expression to represent Malay culture. The connection between content and expression found in this research shows a difficult ratio, which requires encyclopedia and understanding to understand the intentions of the songwriters.